Design and fabrication of glass bottle cutter / Nurul Alya Amanina Mohd Ishak and Ab Aziz Mohd Yusof - Mohd Ishak, Ab Aziz; Mohd Yusof, Mohd Ishak (School of Mechanical Engineering, 2022)
This project was carried out with two objectives. The first objective was to design a prototype of a glass bottle cutter machine and the second objective was to fabricate a glass bottle cutter machine based on the designed prototype. The glass bottle cutter machine is capable of helping the community to reproduce new products like drinking glass, ashtray, and vases based on the recycled bottles. It can be placed at the recycling service store or craft shop. The design of the glass bottle cutter varies from others as it is heavy-duty and long-lasting. With the scope to cut the bottle clean and safe for reuse and recycling, the design and fabrication process went through several processes. Started with brainstorming for the suitable cutting mechanism before proceeding with the fabrication process including measuring, cutting, welding, and drilling. This glass bottle cutter is made from metals, operated by a DC motor for the cutting purpose and rotation of the wheel and diamond blade as the cutting tool. The cutting tool was a diamond blade instead of a wheel cutter which helps to decrease the requirement of human forces. Test results show the glass bottle is able to be cut in less than 1 minute. As compared to the existing glass bottle cutter, it is done manually, the user is required to score the glass bottle with a wheel cutter and immerse the glass bottle in hot and cold water for 1 minute respectively. This shows that it is such a long process and the existing product itself does not last longer for cutting a number of the glass bottles. The machine provides an alternative to less human forces and has fine cutting-edge finishing. To conclude, the fabrication of a glass bottle cutter machine based on the design and analysis of the prototype achieved the mentioned objectives. Some recommendations can be added as an initiative to improve this glass bottle cutter machine such as adding a safety button, applying coolant to prevent the glass dust from shattering all over the place, and providing the function of polishing the cutting edge.